Literasi Digital Dan Perempuan - Mira Veranita (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Abstract The empowerment of women, especially in digital literature, has a very important role in the development of the nation's well-being, especially as a dynamizer, a window of information and supporting the family's economic resilience. Women have the same rights as men to develop and adapt to the developments of information technology, thus developing digital literacy insights and developing horizons and insights in building families, providing knowledge and information to families about all kinds of things such as education, health, economics, and economics as well as protecting families from information and negative influences. Keywords : Women; Literacy; Digital Abstrak Pemberdayaan perempuan terutama dalam literasi digital memiliki andil yang cukup penting dalam pembangunan kesejahteraan bangsa, terutama kiprahnya sebagai dinamisator, jendela informasi dan menopang ketahanan ekonomi keluarga. Perempuan memiliki hak yang sama dengan laki-laki untuk berkembang dan beradaptasi dengan perkembangan teknologi informasi sehingga berkembang wawasan literasi digital dan berkembang juga cakrawala dan wawasan dalam membangun keluarga, memberikan pengetahuan dan informasi bagi keluarga mengenai berbagai hal baik itu pendidikan, kesehatan, ekonomi, ekonomi serta memproteksi keluarga dari informasi dan pengaruh negatif. Kata Kunci : Perempuan; Literasi; Digital